Kesenjangan Program Kesehatan dan Kebutuhan Aktual Lansia di Panti Jompo Al-Ishlah - Clarissa Aldora Simamora; Fin Fina Marsita Ziporani Daniela Ballo; Iqbal Abdan Syakuran Achmad; Rizky Dwi Nugroho; Neza Sabilla (Institut Nalanda, 2026)
This study aims to evaluate the health programs at the Al-Ishlah Nursing Home and identify the gap between the services available and the actual health needs of the elderly. The research used a qualitative approach with a case study design through participatory observation in morning gymnastics activities and semi-structured interviews with 12 informants consisting of managers, nurses, and the elderly. Data were analyzed using thematic analysis to identify key themes that emerged from the health experiences and needs of nursing home residents. The results of the study show that existing health programs have supported the physical, social, and spiritual well-being of the elderly. However, there was a discrepancy between the program's focus on general physical health and the actual needs of the elderly who were dominated by heart disease and vision impairment due to cataracts. These findings show the need for adjustments to health programs that are more responsive to non-communicable diseases in the elderly. Research recommends increased government support as well as the development of health programs that focus on the early detection, monitoring, and ongoing management of heart disease and cataracts.